1990
DOI: 10.1136/bmj.301.6743.83
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment to a prospective breast conservation trial: why are so few patients randomised?

Abstract: Objective-To investigate the rate of recruitment to early breast cancer trials and elucidate the reasons for ineligibility and refusal to participate among patients otherwise suitable for these trials.Design

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 6 publications
1
32
0
Order By: Relevance
“…The applicability of the trial results is highly dependent on the selection that occurs in each step. Entry rates of patients for RCTs and the reasons for non-entry have been studied by a number of groups (McCusker et al, 1982;Lee and Breaux, 1983;Martin et al, 1984;Anonymous, 1986;Jack et al, 1990;Fentiman et al, 1991;Gorst and Johnson, 1992;Kotwall et al, 1992;Kober and Torp-Pedersen, 1995;Partonen et al, 1996;Licht et al, 1997) but the effect of selection on the applicability of the trial results has been investigated in only a few, mainly pharmaceutical studies (Anonymous, 1986;Gorst and Johnson, 1992;Kober and Torp-Pedersen, 1995;Licht et al, 1997). To our knowledge, the effect of patient selection on applicability of results in surgical/radiotherapy trials has never been fully analysed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The applicability of the trial results is highly dependent on the selection that occurs in each step. Entry rates of patients for RCTs and the reasons for non-entry have been studied by a number of groups (McCusker et al, 1982;Lee and Breaux, 1983;Martin et al, 1984;Anonymous, 1986;Jack et al, 1990;Fentiman et al, 1991;Gorst and Johnson, 1992;Kotwall et al, 1992;Kober and Torp-Pedersen, 1995;Partonen et al, 1996;Licht et al, 1997) but the effect of selection on the applicability of the trial results has been investigated in only a few, mainly pharmaceutical studies (Anonymous, 1986;Gorst and Johnson, 1992;Kober and Torp-Pedersen, 1995;Licht et al, 1997). To our knowledge, the effect of patient selection on applicability of results in surgical/radiotherapy trials has never been fully analysed.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies report rates of eligible but non-entered patients of 25 -73% (Lee and Breaux, 1983;Jack et al, 1990;Kotwall et al, 1992). The five institutes selected for our study are all specialised cancer centres and the physicians have put much effort into randomisation of suitable cases with only a few patients not being considered for entry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32,33 They can also be affected by pre-existing factors such as the beliefs of the collaborating clinicians 34 and patient preferences. 35,36 Several such factors have been reported as barriers to recruitment by trialists 37,38 and identified in empirical studies. 15,39,40 These forces create a complex microclimate in which a trial can flourish, struggle, or do both.…”
Section: Introductionmentioning
confidence: 99%
“…Trials conducted in the UK showed that 45% failed to reach 80% of the target and it is more worrying that less than half of participating physicians succeeded in recruiting any patients. 10,11 Clinical trials conducted in the UK between 1971 and 2000 (n-333) revealed that just over one-half failed to recruit the desired sample size, one-fifth recruited at least 75% of the target sample, while a further fifth recruited 25% of the planned number of patients. 12 Another concern is that the number of physicians pursuing a career in research has also declined.…”
mentioning
confidence: 99%